Endemic earthworms (Oligochaeta: Lumbricidae) of the Balkan Peninsula: a review - Trakić, Tanja; Valchovski, Hristo; Stojanović, Mirjana (Zootaxa, 2016)
A list of the endemic earthworms of the Balkan Peninsula is presented. Comprehensive information on the ecology, distribution on the Balkan Peninsula and zoogeographical type of all endemics is given. The list comprises 90 species and subspecies, belonging to 11 genera of the family Lumbricidae. The largest number of the Balkan endemic earthworms belongs to a narrow range group (63.3%). Broad range endemic species take part with 36.7%. Our study shows that the degree of endemism on the Balkan Peninsula is extremely high (about 40%) suggesting an important process of autochthonous speciation on the Balkan Peninsula. This appearance is attributable to relative isolation of the mountains compared to the lowlands within the context of paleoenvironmental changes.